2013
DOI: 10.1371/journal.pone.0079743
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Two Lysozyme Genes and Antimicrobial Functions of Their Recombinant Proteins in Asian Seabass

Abstract: Lysozymes are important proteins of the innate immune system for the defense against bacterial infection. We cloned and analyzed chicken-type (c-type) and goose-type (g-type) lysozymes from Asian seabass (Lates calcarifer). The deduced amino acid sequence of the c-type lysozyme contained 144 residues and possessed typical structure residues, conserved catalytic residues (Glu50 and Asp67) and a “GSTDYGIFQINS” motif. The deduced g-type lysozyme contained 187 residues and possessed a goose egg white lysozyme (GEW… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
22
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(24 citation statements)
references
References 53 publications
(100 reference statements)
1
22
0
Order By: Relevance
“…Lysozyme activity provides an insight into the immune response of fish [32,41]. Results indicated an increase in serum lysozyme activity of both fish groups fed on onion and barley extracts.…”
Section: Discussionmentioning
confidence: 99%
“…Lysozyme activity provides an insight into the immune response of fish [32,41]. Results indicated an increase in serum lysozyme activity of both fish groups fed on onion and barley extracts.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, in CiLys-g3 all three catalytic residues (Glu, Asp, Asp) responsible for the binding of the lysozyme to the bacterial cell wall turned out to be highly conserved (Fu et al, 2013) whereas in CiLys-g1 and CiLys-g4, only two catalytic residues (Glu, Asp) were found to be conserved. Structure and surface analysis revealed that the conserved GXXQ motif among the Cilys-g lysozymes is located nearer to the hydrophobic core region.…”
Section: Discussionmentioning
confidence: 98%
“…Since the starry flounder c-type lysozyme contains aspartic acid residues at positions 100 and 101 that have been known to be necessary for calcium binding, it may belong to the calcium binding family, likely with mammalian and avian orthologues [30][31][32]. G-type lysozyme in starry flounder possesses conserved residues essential for catalytic activity, which would be commonly observed in orthologues from various animal species [2,5,8]. In the alignment, Glu 72 and Asp 96 (starry flounder numbering) are conserved in all species, whereas the Asp 85 residue is present in all teleostean sequences except common carp Cyprinus carpio [5,8,[33][34][35].…”
Section: Discussionmentioning
confidence: 99%
“…G-type lysozyme in starry flounder possesses conserved residues essential for catalytic activity, which would be commonly observed in orthologues from various animal species [2,5,8]. In the alignment, Glu 72 and Asp 96 (starry flounder numbering) are conserved in all species, whereas the Asp 85 residue is present in all teleostean sequences except common carp Cyprinus carpio [5,8,[33][34][35]. Unlike its c-type counterpart, starry flounder g-type lysozyme has no potential cysteine residues capable of disulfide bridging, which is congruent with most other piscine g-type orthologues [4,5,7,8,[33][34][35][36].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation